Perancangan Komunikasi Visual Museum Negeri Mpu Tantular Melalui Buku Fotografi Sebagai Upaya Menginformasikan Koleksi Unggulan Museum - Sholekhah, Risna Awalia; Budiardjo, Hardman; Yurisma, Dhika Yuan (Jurnal Art Nouveau, 2017)
Museum is one of essential parts regarding tourism industrial especially for historical and cultural tourism. One of the museum that existed in East Java is MuseumNegeri Mpu Tantular that legitimately established at July 25th 1937. This museum owns numerous historical collection. Beside the existed collections, it has special considered collection coming from various zone. However, the collections’ great quantity frequently makes the visitor don’t pay much attention to the special considered collections. According to the aforementioned statement, visual communication through photography book which explains the distinctive collections is clearly needed. This kind of book is expected to clearly and completely inform to the visitor not only about the origin but also the background history from each distinctive collection which is owned by Museum Negeri Mpu Tantular. The method used by utilizing a qualitative research method that starts from collecting data through interviews, observation, documentation, study litelatur, study competitors, until the conclusion. Resulting design photography book with key massage "masterpiece" that has superior meanings or different from the others. Photography books that have been designed to have a visual element that is able to inform the State Museum Negeri Mpu Tantular. Keywords: Design, Visual Communication, Design, Visual Communication,  Books Fotography , the State Museum MPU Tantular, Masterpiece, Information